Polygamy as a Social Anomaly: Muhammad Shahrur's Progressive Interpretation of Quranic Family Law - Lufaefi, Lufaefi (Tasyri' : Journal of Islamic Law, 2026)
Polygamy is one of the central themes in Islamic studies that has continuously sparked debate, both within the realm of Qur’anic exegesis and in social discourse. In classical tafsir tradition, polygamy is understood as a permissible practice regulated by the Sharia, with justice as its primary condition. However, historical realities and social practices often reveal that such justice is difficult to achieve, thus generating social, psychological, and gender-related problems. The development of modern thought has introduced new perspectives in understanding polygamy. Some contemporary exegetes emphasize maqāṣid al-sharī‘ah to reinterpret Qur’anic verses on polygamy in accordance with the principle of substantive justice. This research focuses on the analysis of Muhammad Shahrur’s progressive exegesis, a modern Muslim thinker who offers a contextual approach to the Qur’anic text. Through a library research method, this study examines Shahrur’s works and compares them with classical interpretations. The findings indicate that Shahrur views polygamy as a form of dispensational ruling that is emergency-based and contextual, rather than a universally applicable norm. Thus, polygamy is positioned as a situational solution limited to specific conditions, not as a recommended rule. These findings highlight that progressive exegesis provides a more responsive interpretive framework to address contemporary issues such as gender equality and human rights. This research also opens critical discussions on the relevance of polygamy in modern society, while emphasizing the importance of Qur’anic interpretation that is contextual, inclusive, and grounded in justice.